2002
DOI: 10.1159/000057792
|View full text |Cite
|
Sign up to set email alerts
|

The Endolymphatic Sac: A Scanning and Transmission Electron Microscopy Study

Abstract: A recent investigation has suggested that the chief cells of the endolymphatic sac produce an endogenous inhibitor of sodium resorption in the kidneys, tentatively named saccin. In the current study, the ultrastructure of the endolymphatic sac and in particular the chief cells are described to demonstrate that this organ fulfils the morphological criteria of a potential endocrine gland. Accordingly, the chief cells are shown to exhibit all the organelles and characteristics of cells that simultaneously synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…One may definitely speculate on a possible endocrine function, as suggested in previous papers, maybe as a local function involving the mitochondria‐rich cells, as a response to altered endolymph volume or changes in intracranial pressure. The presence of fenestrated capillaries supports the hypothesis of a potential endocrine function and is consistent with ultrastructural observations in animal studies . These observations could indicate the existence of a hormonal feedback system, which also was suggested in a recent animal study, in which the hormone angiotensinogen was found in the rat ES .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One may definitely speculate on a possible endocrine function, as suggested in previous papers, maybe as a local function involving the mitochondria‐rich cells, as a response to altered endolymph volume or changes in intracranial pressure. The presence of fenestrated capillaries supports the hypothesis of a potential endocrine function and is consistent with ultrastructural observations in animal studies . These observations could indicate the existence of a hormonal feedback system, which also was suggested in a recent animal study, in which the hormone angiotensinogen was found in the rat ES .…”
Section: Discussionsupporting
confidence: 90%
“…These studies overall show evidence of transcellular water transport through several different aquaporin channels located in the epithelial cells, potentially initiated by vasopressin, through its receptor located in the ES epithelium. Previously described mitochondria‐rich cells in the ES are speculated to have a key role in water transport, possibly driving the sodium‐potassium adenosine triphosphatases (Na + , K + ‐ATPases), the Na + ‐H + exchanger, as well as the two Na + ‐K + 2Cl cotransporters recently demonstrated in the human ES . In addition, the ES has been proposed to synthesize a natriuretic compound, and ultrastructural analysis has previously demonstrated morphology compatible with an endocrine activity .…”
Section: Introductionmentioning
confidence: 99%
“…The FORE cell, here genetically defined, has many similarities with a morphologically identified cell type called 'mitochondria-rich' cell. (Qvortrup and Bretlau, 2002). We would like to speculate that the FORE cell could prove to play a role in diseases characterized by altered endolymph turnover/composition, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These macromolecules are taken up and degraded by free-floating cells such as luminal macrophages and lymphoid cells. The ES is believed to play an important role in maintaining homeostasis in the inner ear, by the absorption and secretion of endolymph (Kimura and Schuknecht, 1965;Lundquist, 1965;Friberg et al, 1986;Erwall et al, 1988;Rask-Andersen et al, 1999), pressure regulation in the endolymphatic compartment (Rask-Andersen et al, 1987), immunodefense of the inner ear (Rask-Andersen and Stahle, 1980;Tomiyama and Harris, 1986), the removal of waste products and foreign materials from the endolymphatic space (Fukazawa et al, 1991), and endocrine function (Qvortrup and Bretlau, 2002).…”
Section: Introductionmentioning
confidence: 99%